Strategic Judicial Protection of Public Interests: Legal Aspects - KIRILLOVA, Elena Anatolyevna; BOGDAN, Varvara Vladimirovna; BLINKOV, Oleg Evgenyevich; KOZHINA, Yuliya Alekseevna; YUNUSOVA, Kseniya Vasilyevna (Journal of Advanced Research in Law and Economics, 2018)
This article discusses the features of strategic judicial protection of public interests. Public interest law has the potential to become a common language which can be spoken by various social forces pursuing different goals, but sharing a common interest in building a truly legal state and improving the protection of citizens. The main objective of the research is the analysis of the category of ‘the right of public interest’ and the consideration of the role of strategic judicial protection of public interests. When writing the article, we used the methods of collection and study of single facts; the generalization methods; the methods of scientific abstraction; the methods of cognition of regularities. The conducted research allows introducing into scientific circulation the author's definition of the ‘public interest law’; the work sets the basic features of public interest as a legal category, it is concluded that strategic lawsuits are a form of judicial protection of public interests, which are conducted in the interests of a citizen or a group of citizens, with the aim to achieve systemic changes in the legal field for the benefit of society (in particular, the improvement of the legislative base of the country) and is used to create court practice (precedents). The strategic litigation regarding the public interest should apply the settlement arrangements – negotiation, mediation, judicial conciliation, the settlement agreement. It is proposed in the submission by the parties of documents of statistical and financial nature to use the conciliation procedure – the verification of the calculations, which will allow reconciling the parties and undertaking the necessary legal reforms of the society. It is required to ensure that the results of the reconciliation in such cases can only be a complete rejection of the claim, its full recognition, recognition of circumstances on which the other party based its claims or objections, the agreement in the circumstances of the case.